Emergent endoscopic ultrasonography‐guided antegrade treatment for acute biliary pancreatitis in a patient with altered gastrointestinal anatomy. Issue 3 (10th February 2019) - Hashimoto, Shinichi; Fujita, Toshihiro; Ido, Akio
Abstract : Watch a video of this article